Integrative Exploration Of Problem-Based Learning And Artificial Intelligence In Language Education - Harputra, Yuswin; Ramadhani, Yulia Rizki (ETANIC Journal Of English Language Teaching And Applied Linguistics, 2025)
This integrative literature review examines the potential synergy between Problem-Based Learning (PBL) and Artificial Intelligence (AI) in improving university students’ reading comprehension within language education. Based on 276 selected articles, the analysis highlights three key themes: PBL's role in fostering critical reading, AI's function in personalizing language learning, and the importance of instructional design in linking both approaches. Findings show that while PBL and AI each contribute meaningfully, their integration in language education is rare and lacks systematic application. Major gaps include the absence of tested instructional models, limited evaluation tools, and a shortage of empirical studies in Southeast Asia. The study recommends developing theory-based integrative instructional models and conducting localized research to support effective implementation.